Quality-adjusted life years lost to road crash injury: Updating the Injury Impairment Index - Spicer, R.; Miller, T.; Hendrie, Delia; Blincoe, L. (Association for the Advancement of Automotive Medicine, 2011)
The Injury Impairment Index (III) has long been used internationally to estimate the quality-adjusted life year (QALY) losses associated with crash injuries. The III has major limitations, notably its lack of detailed validation, but it is widely used and estimates from it are regularly published. It is based on physician estimates of typical impairment on 6 dimensions of functioning (cognitive, mobility, bending/grasping/lifting, sensory, pain and cosmetic), supplemented with data on work-related disability. This paper reports on a literature synthesis used to update the III scoring algorithm that converts impairment levels by dimension into a combined QALY loss score. An extensive international literature search identified 13 health status scales, some of them with multiple scorings. From the scorings, we extracted utility scores for each level of each dimension of the III. We also searched for direct utility estimates for III dimension endpoints (e.g., blindness, deafness). Median and inter-quartile ranges were computed by scale point to represent the uncertainty range of preference weights within each III dimension and level. Average QALY losses per injury by MAIS were computed using the updated preference weight ranges applied to 2000-2006 U.S. crash data. The updated QALY loss estimates are lower than those computed with the QALY weights developed in 1990. This paper’s tables of estimated average QALY losses by MAIS, injury type, and body region injured can be applied to future and existing injury data in order to estimate the impact of injury on quality of life and measure health status.